Identification of Ectoparasites in Pearl Catfish (Clarias gariepinus) One and Three Months Ages in Makalele Cultivation Tuban District, Tuban Regency - Galuh Swa Ardhya; Azizatun Nimah; Hani Plumeriastuti; Setiawan Koesdarto; Budiarto Budiarto (Journal of Parasite Science)
ABSTRACT